Fetal echocardiographic assessment of cardiovascular impact of prolonged support on EXTrauterine Environment for Neonatal Development (EXTEND) system. (31st March 2020) - Ozawa, K.; Davey, M. G.; Tian, Z.; Hornick, M. A.; Mejaddam, A. Y.; McGovern, P. E.; Flake, A. W.; Rychik, J.
ABSTRACT: Objective: EXTrauterine Environment for Neonatal Development (EXTEND) is a system to support ongoing fetal growth and organ development in an extrauterine environment, utilizing a pumpless low‐resistance oxygenator circuit. The aim of this study was to evaluate hemodynamics and cardiac function in fetal sheep sustained on the EXTEND system. Methods: This was a prospective study of fetal sheep supported for a minimum of 3 weeks on EXTEND. Hemodynamic parameters were assessed weekly and included heart rate, mean arterial pressure (MAP), Doppler‐echocardiography‐derived cardiac output (CO), pulsatility indices (PIs) of the fetal middle cerebral artery (MCA), umbilical artery (UA) and ductus venosus and cardiac function, as assessed by speckle‐tracking‐derived global longitudinal strain and strain rate in the right (RV) and left (LV) ventricles. Parameters were compared at 0 days and 1, 2 and 3 weeks following placement on EXTEND. Results: Of 10 fetal sheep enrolled, seven survived for 3 weeks and were included in the analysis. Median gestational age at cannulation was 107 (range, 95–109) days. Heart rate decreased and MAP increased significantly, but within acceptable ranges, during the study period. The quantities and relative ratios of right and left CO remained stable within the anticipated physiological range throughout the study period. Vascular tracings and PIs appeared to be similar to those seen normally in the natural in‐utero state, with MCA‐PI being higher than UA‐PI. UA tracings demonstrated maintained abundant diastolic flow despite the absence of placental circulation. In both the RV and LV, strain decreased significantly at 1 and 2 weeks relative to baseline but returned to baseline values by week 3. Conclusions: The EXTEND mechanical support system replicates natural physiology and creates a stable and sustainable cardiovascular construct that supports growth over a 3‐week period. However, there is a period of depressed contractility within the first week with subsequent improvement by week 3. This may reflect a period of physiological accommodation that warrants further investigation. This study lays the foundation for further exploration as the EXTEND system moves towards human application. © 2019 The Authors. Ultrasound in Obstetrics & Gynecology published by John Wiley & Sons Ltd on behalf of the International Society of Ultrasound in Obstetrics and Gynecology.